Unique accessories you can make and share - Bolte, Mari (North Mankato, Minnesota Capstone Press, 2016)
"Step-by-step instructions, tips, and full-color photographs will help teens and tweens create fun accessories"--
A gift from book Africa
Handcraft
1 2 13 15
NEW_ZTN_GN
Keywords: Dress accessories -- Juvenile literature; Handicraft for girls; Handicraft for girls